1994
DOI: 10.1080/00039896.1994.9955002
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Consequences of Exposure to Wood Dust and Formaldehyde of Workers Manufacturing Oriented Strand Board

Abstract: A cross-sectional study was performed at a plant in which 99 workers were employed in the manufacture of oriented strand board. This group was compared with 165 unexposed workers from the petroleum industry. Both groups were assessed, using a questionnaire, spirometry, and skin prick tests to common environmental antigens. Environmental studies showed a low dust level of 0.27 mg/m3, consisting of particles of a mass median aerodynamic equivalent diameter of 2.5 microns. There were variable concentrations of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…1,2 For the traditional conversion of wood into composite-materials, industrial processes employ either heterogeneous chemical (graft) modification (wood functionalization), or the use of toxic phenol or formaldehyde-based adhesives for wood particles such as in the case of OSBs (Oriented Strand Boards) and MDFs (Medium Density Fibreboards). 3 Performing these processes leads to the unavoidable consumption of large amounts of energy and expensive chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 For the traditional conversion of wood into composite-materials, industrial processes employ either heterogeneous chemical (graft) modification (wood functionalization), or the use of toxic phenol or formaldehyde-based adhesives for wood particles such as in the case of OSBs (Oriented Strand Boards) and MDFs (Medium Density Fibreboards). 3 Performing these processes leads to the unavoidable consumption of large amounts of energy and expensive chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…However, review authors noted a limitation with Billionnet et al [53] in that no estimates of statistical confidence (i.e., standard error, 95% confidence interval) were reported with these estimates. Although all four studies reported increased odds with increased category of exposure, only Herbert et al [76] reported a statistically significant increase (comparing exposed versus non-exposed occupational groups). Similarly, the scatterplot of prevalence data by formaldehyde exposure categories demonstrated a similar pattern of supporting increases in asthma prevalence with increasing formaldehyde exposure (S11 Fig) . For instance, Elshaer and Mahmoud [47] reported dramatic prevalence increases in exposed occupational workers for asthma (53.3%) versus non-exposed workers.…”
Section: Plos Onementioning
confidence: 89%
“…reporting statistically significant findings (S9 and S10 Figs). For instance, Herbert et al [76] reported a statistically significant increase in asthma symptoms (attacks of wheeze) comparing exposed versus non-exposed occupational groups. Asthma prevalence estimates were generally greater with increased exposure to formaldehyde, but these studies lacked confidence intervals around the point estimates (S11 Fig).…”
Section: Plos Onementioning
confidence: 99%
“…Thirteen occupational studies investigating associations between exposures to particles during a full work shift and FEV 1 and FVC changes were included [33,[44][45][46][47][48][63][64][65][66][67][68][69]. All thirteen studies measured FEV 1 , while eight also assessed FVC.…”
Section: Occupational Studiesmentioning
confidence: 99%
“…FEV1 and PM4 in occupational studies Panel (b) of Figure 2 shows the forest plot for eight occupational studies that reported associations between short-term exposure to PM 4 and FEV 1 in mL change. Across these studies, the exposure levels varied from 270 µg/m 3 (wood dust exposure; Herbert et al (1994) [63]) and 2390 µg/m 3 (cotton dust exposure; Bakirci et al (2007) [45]). A negative association was observed, but the meta-estimate was lower compared to environmental studies; a 10 µg/m 3 increase in PM 4 concentration was associated with a reduction of 0.87 mL (95% CI: −1.36 to −0.37 mL) in FEV 1 after a work shift.…”
mentioning
confidence: 99%